2013
DOI: 10.1016/j.matdes.2012.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment effect on thermo-mechanical fatigue and low cycle fatigue behaviors of A356.0 aluminum alloy

Abstract: a b s t r a c tIn the present paper, the heat treatment effect on A356.0, a cast aluminum alloy which has been widely used in diesel engine cylinder heads, is investigated under out-of-phase thermo-mechanical fatigue and low cycle fatigue (at different temperatures) loadings. A typical heat treatment is applied to the material including 8 h solution at 535°C, water quench and 3 h ageing at 180°C. The experimental fatigue results show that the heat treatment process has considerable influence on mechanical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 26 publications
3
37
0
1
Order By: Relevance
“…It is found that whether IP or OP TMF test, the greater the mechanical strain amplitude, the wider the stress‐strain hysteresis loop and the greater the plastic strain. It is known that the increment of plastic strain presents a cyclic softening behavior of the material under strain‐controlled loading . Moreover, The area of hysteresis loop represents the dissipated plastic deformation energy per cycle, which can cause TMF damage and therewith be used as a phenomenological damage parameter, similar as plastic strain amplitude in the Manson‐Coffin representation of lifetime behavior .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that whether IP or OP TMF test, the greater the mechanical strain amplitude, the wider the stress‐strain hysteresis loop and the greater the plastic strain. It is known that the increment of plastic strain presents a cyclic softening behavior of the material under strain‐controlled loading . Moreover, The area of hysteresis loop represents the dissipated plastic deformation energy per cycle, which can cause TMF damage and therewith be used as a phenomenological damage parameter, similar as plastic strain amplitude in the Manson‐Coffin representation of lifetime behavior .…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the increment of plastic strain presents a cyclic softening behavior of the material under strain-controlled loading. 16,17 Moreover, The area of hysteresis loop represents the dissipated plastic deformation energy per cycle, which can cause TMF damage and therewith be used as a phenomenological damage parameter, similar as plastic strain amplitude in the Manson-Coffin representation of lifetime behavior. 18 Obviously, TMF damage becomes more and more serious with increasing mechanical strain amplitude.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Magnesium is an important element which forms a significant solid solution in Al-Si alloys and increases the strengths of alloys with precipitation hardening. A356 alloys constitute the most important group of Al-Si-Mg alloys whose strength can be increased with Mg 2 Si precipitates in Al matrix [2][3][4][5]. Another important method used to improve the mechanical properties of the alloy is to compose stable in situ intermetallic phases in the structure [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum alloys are at the center of the search since they offer considerable opportunity to design lightweight vehicles. Although Al alloys have good castability, corrosion resistance, low coefficient of thermal expansion and high strength to weight ratio [1][2][3] their main challenge is their strength at temperatures above 200°C. Above this temperature, the phases present in the microstructure which strengthen the alloy usually coarsen or dissolve resulting in reduction of high temperature performance [4,5].…”
Section: Introductionmentioning
confidence: 99%